Response of Banana to Drip Irrigation under Different Irrigation Designs - Pattanaik, S K; Sahu, N N; Pradhan, P C; Mohanty, M K (Journal of Agricultural Engineering, 2003)
Field experiment was carried out on the lateritic sandy loam soil of Bhubaneswar, Orissa to evaluate the economic feasibility of drip irrigation with black LDPE (Low Density Polyethylene) mulch field of different levels of irrigation for Banana crop. Out of eight treatments, six treatments are of drip irrigation with three levels of irrigation (V, 0.8V, 0.6V) and two treatments are of basin irrigation. The study indicated that better plant growth, early emergence of flower and enhancement in the yield under drip irrigation with plastic mulch. The highest yield (525.33 quintal) was recorded under drip irrigation (0.8 V) with mulch (T6) as compared to other treatments. An increase of 52% in banana yield and 54% in net seasonal income were recorded in case of 80% irrigation requirement of drip irrigation with mulch as compared to conventional ring basin irrigation. Benefit cost ratio was also found to be highest for the same treatment and at par with that of the conventional basin irrigation. Water use efficiency was found to be highest under drip irrigation (0.8V) with mulch (T6) followed by drip irrigation (0.6V) with mulch (T7).